2016
DOI: 10.2106/jbjs.15.01017
|View full text |Cite
|
Sign up to set email alerts
|

Preseason Assessment of Radiographic Abnormalities in Elbows of Little League Baseball Players

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
0
29
1
Order By: Relevance
“…Prior research has shown that overhead athletes, particularly baseball players, may be asymptomatic but still have abnormalities on MRA. 22 , 30 , 42 Thus, the combination of a clinical examination was required to make the diagnosis of a UCL injury. It should be noted that ultrasonography with an experienced operator is another imaging modality that can be used to make a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that overhead athletes, particularly baseball players, may be asymptomatic but still have abnormalities on MRA. 22 , 30 , 42 Thus, the combination of a clinical examination was required to make the diagnosis of a UCL injury. It should be noted that ultrasonography with an experienced operator is another imaging modality that can be used to make a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 Multiple potential risk factors may be responsible, including year-round play, pitching for more than 1 team, pitch velocity, player height and weight, and loss of shoulder internal rotation. 1,9,18,19,22…”
mentioning
confidence: 99%
“…11 In relation to this, it has recently been shown that more than one-third of Little League baseball players had abnormal preseason magnetic resonance imaging findings of the elbow. 15 Pitching is a common mechanism of injury in baseball. 5,14 Olsen et al 14 found that adolescent pitchers with injuries to the shoulder and elbow pitched significantly more months per year, games per year, innings per game, pitches per game, pitches per year, and warm-up pitches per game.…”
mentioning
confidence: 99%